Սվեդիահայ-մուսալեռցի ինքնութեան դրսեւորումներ եւ կենսապահովման մշակոյթի առանձնայատկութիւններ - Պօղոսեան, Սվէտլանա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Мусалерцы до 1915 года, проживая в маленькой провинции Суедия, были известны как суедские армяне. В дни самообороны и в последующие первые годы битвы были известны под названием Суедского восстания. Впоследствии жители начинают воспринимать себя мусалерцами и термин «суедский армянин» употребляется преимущественно, когда говорят о прошлом. Кроме выражения суедцы употребляли также: народ Мусадага, Муса лера, мусадагцы. После возвращения в Мусалер постепенно начинают употреблять название мусадагец/ мусалерец, которое дошло до наших дней. Before 1915, the inhabitants of Musaler were known as Suedian Armenians, living in the small province of Suedia. In times of self-defense and in the following years, the fighting was called the Suedian uprising. Thereafter, the population perceived themselves as the Musaler people and used the term “Suedian Armenians” mostly when talking about the past. Along with the expression “the people of Suedia”, they also used definitions such as the people of Musadag, Musaler. After returning to Musaler, the expression “the people of Musadag/Musaler” came into practice and is still used today.
Keywords: Պատմաբանասիրութիւն; Մշակոթային հարմարվողականութին